Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1974
DOI: 10.1055/s-0028-1098601
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Findings of Pancreatic Cysts Diagnosed by Endoscopic Pancreatocholangiography

Abstract: In 32 cases pancreatic cysts were diagnosed by endoscopic pancreatocholangiography (ERPC) all confirmed by subsequent surgery. From the X-ray findings, we can enumerate the following symptoms as being typical of or at least suspicious for pancreatic cysts: I. Direct filling of cyst cavity. 2. Filling defect in the pancreatic branches and parenchyma. 3. Obstruction of the main pancreatic duct as a strict or as a tapering type abruption. 4. Displacement and compressions of the common bile duct. Pancreatic cysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Seifert et al (76) reported in 32 cases, the following findings could be enumerated as typical of, or at least suggestive of a pancreatic cyst: direct filling of cyst cavity -filling defect in the pancreatic branches and parenchymaobstruction of the main pancreatic duct as a stricture or as a tapering type, displacement and compression of the common bile duct. They (76) also ob served that pancreatic cysts were located in the head region in 17 cases, and in 15 cases in the tail region, and that a single cyst was seen more often than multiple cysts.…”
Section: Pancreatic Cystmentioning
confidence: 99%
See 1 more Smart Citation
“…Seifert et al (76) reported in 32 cases, the following findings could be enumerated as typical of, or at least suggestive of a pancreatic cyst: direct filling of cyst cavity -filling defect in the pancreatic branches and parenchymaobstruction of the main pancreatic duct as a stricture or as a tapering type, displacement and compression of the common bile duct. They (76) also ob served that pancreatic cysts were located in the head region in 17 cases, and in 15 cases in the tail region, and that a single cyst was seen more often than multiple cysts.…”
Section: Pancreatic Cystmentioning
confidence: 99%
“…They (76) also ob served that pancreatic cysts were located in the head region in 17 cases, and in 15 cases in the tail region, and that a single cyst was seen more often than multiple cysts. Filled cysts without discharge into the main duct must be oper ated on immediately, at least within 10 h of ERCP, due to the danger of puru lent infection (76).…”
Section: Pancreatic Cystmentioning
confidence: 99%
“…In the healing or scarring process, leakage of the duct may be closed a n d E R P C then m a y show complete occlusion of the involved duct. In such changes, which C o t t o n a n d Beales [16] observed in 4 of 25 cases and Seifert et al [15] in 13 of 32 cases, the diagnosis of necrotizing cavity c a n n o t be made by E R P C alone. The pancreatic duct can be displaced and n a r r o w e d by abscesses a n d more distinctly by pseudocysts (Fig.…”
Section: Necrotizing Lesions and Pseudocystsmentioning
confidence: 95%
“…In these conditions ERPC presents several advantages: A reliable diagnosis of necrotizing lesions or pseudocysts can be established, and indication and planning for surgical intervention can be assessed. However, demonstration of a necrotic cavity is an absolute indication for surgical intervention within 24 h after filling, or with a delay of 2 to 3 days if the cavity is quickly emptied [15]. Tryptic liquefaction leads to rupture of the ducts, allowing pancreatic juice to escape into the cavity or beyond the confines of the gland, forming a pseudocyst.…”
Section: Necrotizing Lesions and Pseudocystsmentioning
confidence: 99%
“…The possibility to inspect the papillary region endoscopically and to visualize the biliary as well as the pancreatic system radiologically by direct instillation of dye has opened new ways in the diagnosis of biliary and pancreatic diseases. This was evaluated hitherto by the frequency of positive cannulation of the ampulla of \rater or by the results in special pathological findings in the biliary and pancreatic duct system (1)(2)(3)(4)(5)(6)(7)(8)10).…”
mentioning
confidence: 99%